Sustainable Tourism Destination Management Strategy: Improving Service Quality and Visitor Satisfaction - Ramdhan Kurniawan; Faridah Iriani; Minrohayati Minrohayati (PT. Global Research Collaboration, 2024)
Taman Kota 1 BSD is one of the green open spaces that has great potential to be developed as a sustainable tourism destination. This article discusses sustainable management efforts at Taman Kota 1 BSD which include improving the quality of facilities, empowering local communities, and applying digital technology for promotion and management. Through service activities that actively involve the community, there is a significant increase in key indicators such as visitor satisfaction, community participation, and environmental awareness. Survey results show that facility and service improvements, community training, and the use of digital technology have successfully improved the quality of this tourist destination. In addition, waste management and environmental education programs also contribute to environmental sustainability. With a holistic strategic approach, Taman Kota 1 BSD is expected to continue to be a model of a sustainable tourist destination that provides economic, social, and environmental benefits to the surrounding community.